Konsep Persaudaraan dalam Kasih pada 1 Yohanes 3:11-18 dan Kasih Persaudaraan pada Falsafah Dalihan Na Tolu Suku Batak Toba - Valentino Wariki; Michael Lauw; Yunias Gracia (Universitas Sanata Dharma, 2025)
Christianity understands love as a basic principle of life. In the philosophy of Dalihan Na Tolu and Letter 1 John 3:11-18 there is an essence that can be met. Therefore, the purpose of this article is to provide an understanding of brotherly love based on the perspective of the philosophy of Dalihan Na Tolu and the text of 1 John 3:11-18. In this article, the researcher uses a qualitative method with a literature study approach. The researcher also conducted an exegetical analysis to obtain the substance of love related to Dalihan Na Tolu. The results of this study indicate that Dalihan Na Tolu and 1 John 3:11-18 have something in common, namely the need to build love in brotherly relationships. If Dalihan Na Tolu shows the importance of building a life in love for fellow brothers, then letter 1 John 3:11-18 seeks to open the paradigm that every student must be seen as a sibling so that the application of love becomes more dynamic. The meeting point between the two is in the desire to apply brotherly love.